The stability of the RNA bases: Implications for the origin of life - Levy, Matthew (The National Academy of Sciences, 1998)
High-temperature origin-of-life theories require that the components of the first genetic material are stable. We therefore have measured the half-lives for the decomposition of the nucleobases. They have been found to be short on the geologic time scale. At 100°C, the growth temperatures of the hyperthermophiles, the half-lives are too short to allow for the adequate accumulation of these compounds (t(1/2) for A and G ≈ 1 yr; U = 12 yr; C = 19 days). Therefore, unless the origin of life took place extremely rapidly (<100 yr), we conclude that a high-temperature origin of life may be possible, but it cannot involve adenine, uracil, guanine, or cytosine. The rates of hydrolysis at 100°C also suggest that an ocean-boiling asteroid impact would reset the prebiotic clock, requiring prebiotic synthetic processes to begin again. At 0°C, A, U, G, and T appear to be sufficiently stable (t(1/2) ≥ 10(6) yr) to be involved in a low-temperature origin of life. However, the lack of stability of cytosine at 0°C (t(1/2) = 17,000 yr) raises the possibility that the GC base pair may not have been used in the first genetic material unless life arose quickly (<10(6) yr) after a sterilization event. A two-letter code or an alternative base pair may have been used instead.